Ingestion of 10 grams of whey protein prior to a single bout of resistance exercise does not augment Akt/mTOR pathway signaling compared to carbohydrate - Cooke Matthew B; La Bounty Paul; Buford Thomas; Shelmadine Brian; Redd Liz; Hudson Geoffrey; Willoughby Darryn S (Journal of the International Society of Sports Nutrition, 2011)
Abstract Background This study examined the effects of a whey protein supplement in conjunction with an acute bout of lower body resistance exercise, in recreationally-active males, on serum insulin and insulin like growth factor 1 (IGF-1) and Akt/mTOR signaling markers indicative of muscle protein synthesis: insulin receptor substrate 1 (IRS-1), AKT, mammalian target of rapamycin (mTOR), p70S6 kinase (p70S6K) and 4E-binding protein 1 (4E-BP1). Methods In a randomized, double-blind, cross-over design, 10 males ingested 1 week apart, either 10 g of whey protein (5.25 g EAAs) or carbohydrate (maltodextrose), 30 min prior to a lower-body resistance exercise bout. The resistance exercise bout consisted of 4 sets of 8-10 reps at 80% of the one repetition maximum (RM) on the angled leg press and knee extension exercises. Blood and muscle samples were obtained prior to, and 30 min following supplement ingestion and 15 min and 120 min post-exercise. Serum and muscle data were analyzed using two-way ANOVA. Results No significant differences were observed for IGF-1 (p > 0.05). A significant main effect for Test was observed for serum insulin (p < 0.01) at 30 min post-ingestion and 15 and 120 min post-exercise, with no Supplement × Test interaction (p > 0.05). For the Akt/MTOR signaling intermediates, no significant Supplement × Test interactions were observed (p > 0.05). However, significant main effects for Test were observed for phosphorylated concentrations of IRS, mTOR, and p70S6K, as all were elevated at 15 min post-exercise (p < 0.05). Additionally, a significant main effect for Test was noted for 4E-BP1 (p < 0.05), as it was decreased at 15 min post-exercise. Conclusion Ingestion of 10 g of whey protein prior to an acute bout of lower body resistance exercise had no significant preferential effect compared to carbohydrate on systemic and cellular signaling markers indicative of muscle protein synthesis in untrained individuals.